Is the Quota Law (12.711/12) being effective, efficient and efficacious? An analysis followed by an evaluation proposal in light of the Theory of Managerial Public administration (Research, Society and Development, 2021)
Understanding how the Laws, public projects, social programs are in fact impacting society, if they are working and if they are being well evaluated is imperative for the new public manager. The new public administration, since the 1980s, increasingly requires the use of scientific knowledge to validate itself, and one of the tools for this is the use of the efficiency, efficacy and effectiveness model. Therefore, this work sought to carry out an analysis from this perspective of the Quota Law 12.711/12, interpreting works that evaluated it. It was concluded that the Quota Law has been effective with regard to the entry of benefited students in HEIs, and that quota students are having similar academic performance to non-quota students. However, no work has correctly addressed efficiency and effectiveness, generating interpretive distortions of reality favorable to the permanence of the Law, a fact that this article seeks to mitigate by unraveling data on its effectiveness and efficiency. In parallel, a proposal for a tree model was created, which would allow future evaluation of the Law.